VD_FINDINFO Jug / 2022 / 88 vom 29. September 2021 - VD Tribunal cantonal (2021)
ENTRAVE AUX SERVICES D'INTÉRÊT GÉNÉRAL, LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE | 239 CP, 286 CP, 26 al. 1 LCR, 49 al. 2 LCR, 90 al. 1 LCR